Consumer Engagement with Brand Posts on Social Media in Consecutive Stages of the Customer Journey. Issue 1 (2nd January 2020) - Demmers, Joris; Weltevreden, Jesse W. J.; van Dolen, Willemijn M.
ABSTRACT: Brands use social media to engage consumers in all stages of the customer journey. Prior work on consumer engagement with brand-generated content on social networking sites has not taken into account the different needs and gratifications sought by consumers during consecutive stages of customer journeys over time. We propose that what drives consumer engagement with brand posts on social networking sites is contingent on the stage of the customer journey. We test our hypotheses by analyzing over 24, 000 brand posts by event organizers on Facebook. Adopting a multilevel approach, we find that informative posts generate more Likes, shares, and comments in the preconsumption stage, whereas entertaining posts generate more consumer engagement in the postconsumption stage. A higher degree of activation in brand posts is associated with higher engagement in the pre- and postconsumption stage but not in the consumption stage. Finally, we find support for an optimal level of vividness during all stages of the customer journey. These findings suggest that brands can benefit from adapting their content on social networking sites to the stage of the customer journey over time. On a theoretical level, this study deepens the understanding of how brands' activities on social networking sites drive consumer engagement throughout the customer journey and offers an empirical link between the domains of customer journeys and consumer engagement.